Intratympanic steroids injection is effective for the treatment of drop attacks with Ménière's disease and delayed endolymphatic hydrops: A retrospective study. Issue 52 (December 2016) - Liu, Bo; Leng, Yangming; Zhou, Renhong; Liu, Jingjing; Liu, Dongdong; Zhang, Su-Lin; Kong, Wei-Jia
Abstract : Abstract: Drop attack (DA) associated with Ménière's disease (MD) and delayed endolymphatic hydrops (DEH) is not common and may cause life-threatening clinical problems. The intratympanic dexamethasone (ITD) is one of primary treatments for MD or DEH. Our study investigated the effect of ITD on the DA associated with endolymphatic hydrops (EH). We retrospectively reviewed 10 patients with MD- and DEH-associated DA between January 2009 and December 2013 in Outpatient Department of Otolaryngology, Union Hospital, Wuhan, China. Among them, 7 patients (5 cases with MD, 2 cases of DEH) received ITD (4 times, on weekly basis). Further repeated ITD courses or intratympanic gentamicin (ITG) were given if the vertigo was not satisfactorily controlled. The number of DA and status of vertigo control after intratympanic injection were evaluated. After a follow-up study lasting from 19 to 35 months, DA in 5 cases (71.4%) disappeared after initial ITD course. In 2 cases, DA was altogether controlled after an additional intratympanic injection (repeated ITD or/and ITG). This study showed that ITD promises to be a first-line conservative treatment for MD- or DEH-related DA since the steroid possesses no inner-ear toxicity. Furthermore, for MD- or DEH-related DA refractory to ITD, ITG can be an effective alternative.